Latin Dance and Working Memory: The Mediating Effects of Physical Activity Among Middle-Aged and Older Latinos - Aguiñaga, Susan; Kaushal, Navin; Balbim, Guilherme M.; Wilson, Robert S.; Wilbur, JoEllen E.; Hughes, Susan; Buchner, David M.; Berbaum, Michael; McAuley, Edward; Vásquez, Priscilla M.; Marques, Isabela G.; Wang, Tianxiu; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Physical activity (PA) is a promising method to improve cognition among middle-aged and older adults. Latinos are at high risk for cognitive decline and engaging in low levels of PA. Culturally relevant PA interventions for middle-aged and older Latinos are critically needed to reduce risk of cognitive decline. We examined changes in cognitive performance among middle-aged and older Latinos participating in the BAILAMOSTM dance program or a health education group and compared the mediating effects of PA between group assignment and change in cognitive domains. Methods: Our eight-month randomized controlled trial tested BAILAMOSTM, a 4-month Latin dance program followed by a 4-month maintenance phase. A total of 333 older Latinos aged 55+ were randomized to either BAILAMOSTM, or to a health education control group. Neuropsychological tests were administered, scores were converted to z-scores, and specific domains (i.e., executive function, episodic memory, and working memory) were derived. Self-reported PA was assessed, and we reported categories of total PA, total leisure PA, and moderate-to-vigorous PA as minutes/week. A series of ANCOVAs tested changes in cognitive domains at 4 and 8 months. A mediation analysis tested the mediating effects of each PA category between group assignment and a significant change in cognition score. Results. The ANCOVAs found significant improvement in working memory scores among participants in the dance group at month 8 (F 1,328 = 5.79, p = 0.017, d = 0.20), Cohen’s d =0.20), but not in executive functioning (F 2,328 = 0.229, p = 0.80, Cohen’s d=.07) or episodic memory (F 2,328 = 0.241, p = 0.78, Cohen’s d=.05). Follow-up mediation models found that total PA mediated the relationship between group assignment and working memory, in favor of the dance group (β = 0 .027, 95% CI [0.0000, 0.0705]). Similarly, total leisure PA was found to mediate this relationship (β =0.035, 95% CI [ 0.0041, 0.0807]).